2014
DOI: 10.1002/mbo3.224
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nitrite resistance of the cytochrome cbb3 oxidase by cytochrome c ScyA in Shewanella oneidensis

Abstract: Cytochrome c proteins, as enzymes to exchange electrons with substrates or as pure electron carriers to shuttle electrons, play vital roles in bacterial respiration and photosynthesis. In Shewanella oneidensis, a research model for the respiratory diversity, at least 42 c-type cytochromes are predicted to be encoded in the genome and are regarded to be the foundation of its highly branched electron transport pathways. However, only a small number of c-type cytochromes have been extensively studied. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 66 publications
(239 reference statements)
5
43
0
Order By: Relevance
“…We have previously demonstrated that an electron shortage for the cbb 3 oxidase leads to a hyperactive phenotype, as illustrated in a strain deficient of the cytochrome bc 1 complex (Fig. 4B), which functions as a quinol dehydrogenase, mediating electron transfer from the quinol pool to the cbb 3 oxidase1428. Because the cbb 3 oxidase works with electrons either from the cytochrome bc 1 complex or from the Nadi reagents, when electrons are no longer delivered to the cbb 3 oxidase in the absence of the cytochrome bc 1 complex the enzyme exclusively reacts with the Nadi reagents, exhibiting enhanced activity.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…We have previously demonstrated that an electron shortage for the cbb 3 oxidase leads to a hyperactive phenotype, as illustrated in a strain deficient of the cytochrome bc 1 complex (Fig. 4B), which functions as a quinol dehydrogenase, mediating electron transfer from the quinol pool to the cbb 3 oxidase1428. Because the cbb 3 oxidase works with electrons either from the cytochrome bc 1 complex or from the Nadi reagents, when electrons are no longer delivered to the cbb 3 oxidase in the absence of the cytochrome bc 1 complex the enzyme exclusively reacts with the Nadi reagents, exhibiting enhanced activity.…”
Section: Resultsmentioning
confidence: 92%
“…As multiple factors are involved in cAMP homeostasis3133, we reasoned that at least some in their altered abundance or absence may suppress nitrite inhibition. In attempts to identify such factors, a random mutation library was constructed from the wild-type strain using pHGT01, a mariner-based transposon vector derived from pFAC2846. This vector has been not only used for construction of transposon insertion libraries but also applicable for cryptic operon screening because of a robust promoter embedded in the transposable sequence2847.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SOD and peroxidase (POD) activities were measured on the basis of pyrogallol autoxidation and guaiacol as the electron donor, respectively (29,30). Quantitative analysis of cytochrome c oxidase (Cco) was carried out as described previously (31).…”
Section: Methodsmentioning
confidence: 99%